Penerapan Aplikasi Online Exam (ONEX) pada Yayasan Mandiri Smart Education - Wira Harjanti, Trinugi; Setiyani, Hari; Nizar Alfi, Muhamad; Ispoyo Widodo, Ugi (Teknik Informatika, Sistem Informasi dan Teknik Elektro, 2025)
The modernization of education demands efficiency, flexibility, and integrity in examinations, especially in non-formal institutions conducting competency tests for students. As digital transformation progresses, the need for fast, secure, and reliable assessments increases. ONEX addresses this by providing an online examination system with camera- and microphone-based proctoring, enabling real-time monitoring to maintain exam integrity. This system offers flexibility for participants to take exams remotely while ensuring strict supervision. For organizers, ONEX automates registration, question preparation, and evaluation, reducing time, resources, and personnel costs. Additionally, it enhances accessibility for test-takers, minimizing transportation costs and familiarizing them with digital assessments. By integrating modern evaluation methods, ONEX ensures an efficient, transparent, and fair examination process, benefiting both administrators and participants.